Anti-HMGB1 Monoclonal Antibody Ameliorates Immunosuppression after Peripheral Tissue Trauma: Attenuated T-Lymphocyte Response and Increased Splenic CD11b+Gr-1+ Myeloid-Derived Suppressor Cells Require HMGB1 - Xiangcai Ruan; Sophie S. Darwiche; Changchun Cai; Melanie J. Scott; Hans-Christoph Pape; Timothy R. Billiar (Mediators of Inflammation)
Although tissue-derived high mobility group box 1 (HMGB1) is involved in many aspects of inflammation and tissue injury after trauma, its role in trauma-induced immune suppression remains elusive. Using an established mouse model of peripheral tissue trauma, which includes soft tissue and fracture components, we report here that treatment with anti-HMGB1 monoclonal antibody ameliorated the trauma-induced attenuated T-cell responses and accumulation of CD11b+Gr-1+ myeloid-derived suppressor cells in the spleens seen two days after injury. Our data suggest that HMGB1 released after tissue trauma contributes to signaling pathways that lead to attenuation of T-lymphocyte responses and enhancement of myeloid-derived suppressor cell expansion.